Comparison of Nested PCR and RFLP for Identification and Classification of Malassezia Yeasts from Healthy Human Skin - Oh, Byung Ho (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2009)
BACKGROUND: Malassezia yeasts are normal flora of the skin found in 75~98% of healthy subjects. The accurate identification of the Malassezia species is important for determining the pathogenesis of the Malassezia yeasts with regard to various skin diseases such as Malassezia folliculitis, seborrheic dermatitis, and atopic dermatitis. OBJECTIVE: This research was conducted to determine a more accurate and rapid molecular test for the identification and classification of Malassezia yeasts. METHODS: We compared the accuracy and efficacy of restriction fragment length polymorphism (RFLP) and the nested polymerase chain reaction (PCR) for the identification of Malassezia yeasts. RESULTS: Although both methods demonstrated rapid and reliable results with regard to identification, the nested PCR method was faster. However, 7 different Malassezia species (1.2%) were identified by the nested PCR compared to the RFLP method. CONCLUSION: Our results show that RFLP method was relatively more accurate and reliable for the detection of various Malassezia species compared to the nested PCR. But, in the aspect of simplicity and time saving, the latter method has its own advantages. In addition, the 26S rDNA, which was targeted in this study, contains highly conserved base sequences and enough sequence variation for inter-species identification of Malassezia yeasts.